Effect of hot water leaf and bark extract of Swietenia mahagoni against the Culex quinquefasciatus and Aedes aegypti larvae (Asian Journal of Medical and Biological Research, 2022)
Mosquito larvae control is essential to prevent mosquito borne diseases such as dengue, Zika, filariasis and chikungunya. Plant extract has the larvicidal properties with less toxicity to other living creatures and no resistance compared to synthetic chemical pesticides. Effect of hot water leaf and bark extract of a forest tree species (Swietenia mahagoni) against the 3rd instar larvae of Culex quinquefasciatus and Aedes aegypti was studied in vitro using five different concentrations (1-5%) of hot water leaf and bark extracts of Swietenia mahagoni. It was observed that, 5% concentrated hot water leaf extract was the most toxic killing 70% larvae of Culex quiquefasciatus and 50% larvae of Aedesa egypti after 24 hours exposure. Similarly, 5% hot water bark extracts killed 65% and 55% of Culex quiquefasciatus and Aedes aegypti larvae respectively. The minimum LC50, LC90 and LC95 values of hot water leaf extract of Swietenia mahagoni against Culex quinquefasciatus Say and Aedes aegypti (L.) with 95% confidence limits were 2.662, 6.968, 8.70 and 2.128, 4.964, 6.054 respectively after 72 hours of exposure. In hot water bark extract of Swietenia mahagoni against Culex quinquefasciatus Say and Aedes aegypti (L.) with 95% confidence limits after 72 hours of exposure minimum LC50, LC90 and LC95values were 1.780, 6.540, 9.458 and 1.370, 4.570, 6.430. The present investigation revealed the possible utilization of hot water leaf and bark extract of Swietenia mahagoni to control mosquito borne disease. Further study is needed to know the active ingredients of the leaf and bark extract of the experimented plant.Asian J. Med. Biol. Res. 2022, 8 (2), 94-102